Where there is no psychiatrist : a mental health care manual - Patel, Vikram; Hanlon, Charlotte (London : RCPsych Publications, 2017)
Mental illnesses are common and cause great suffering to individuals and communities everywhere in the world, but many health workers are more comfortable dealing with physical illness. This practical manual of mental health care is vital for community health workers, primary care nurses, social workers and primary care doctors, particularly in low-resource settings. This guide gives the reader a basic understanding of mental illness by describing more than thirty clinical problems associated with mental illness and uses a problem-solving approach to guide the reader through their assessment and management. Mental health issues as they arise in specific contexts are described - in refugee camps, in school health programmes, as well as in mental health promotion. The final section helps the reader to personalise for a particular location, for example, by entering local information on voluntary agencies, the names and costs of medicines and words in the local language for symptoms. This product is also available as Open Access.
Title from publisher's bibliographic system (viewed on 16 Jan 2019).
Open Access title.
Keywords: Psychiatry -- Developing countries; Mental illness -- Developing countries